(5x^3 - 14x^2=12x+8):(x+2)
giúp với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(12-2\left(1-x\right)^2=\left(3x-2\right)\left(2x-3\right)\)
\(< =>12-2\left(1-2x+x^2\right)=6x^2-9x-4x+6\)
\(< =>12-2+4x-2x^2=6x^2-13x+6\)
\(< =>10+4x-2x^2-6x^2+13x-6=0\)
\(< =>-8x^2+17x+4=0< =>\orbr{\begin{cases}x=\frac{17-\sqrt{417}}{16}\\x=\frac{17+\sqrt{417}}{16}\end{cases}}\)
b, \(10x+3-5x=4x+12< =>5x+3-4x-12=0\)
\(< =>x-9=0< =>x=9\)
c, \(11x+42-2x=100-9x-22< =>9x+42-100+9x+22=0\)
\(< =>18x+64-100=0< =>18x-36=0< =>x=\frac{36}{18}=2\)
d, \(2x-\left(3-5x\right)=4\left(x+3\right)< =>2x-3+5x=4x+12\)
\(< =>7x-3-4x-12=0< =>3x-15=0< =>x=\frac{15}{3}=5\)
e, \(2\left(x-3\right)+5x\left(x-1\right)=5x^2< =>2x-6+5x^2-5=5x^2\)
\(< =>2x-11+5x^2-5x^2=0< =>2x-11=0< =>x=\frac{11}{2}\)
f, \(-6\left(1,5-2x\right)=3\left(-15+2x\right)< =>-6\left(\frac{3}{2}-2x\right)=3\left(2x-15\right)\)
\(< =>-9+12x-6x+45=0< =>6x+36=0< =>x=-6\)
g, \(14x-\left(2x+7\right)=3x+12x-13< =>14x-2x-7=15x-13\)
\(< =>12x-7-15x+13=0< =>-3x+6=0< =>x=-2\)
h, \(\left(x-4\right)\left(x+4\right)-2\left(3x-2\right)=\left(x-4\right)^2\)
\(< =>x^2-16-6x+4=x^2-8x+16\)
\(< =>x^2-6x-12-x^2+8x-16=0\)
\(< =>2x-28=0< =>x=\frac{28}{2}=14\)
q, \(4\left(x-2\right)-\left(x-3\right)\left(2x-5\right)=?\)thiếu đề
Câu a : \(4x^3-5x^2+6x+9\)
\(=4x^3+3x^2-8x^2-6x+12x+9\)
\(=\left(4x^3+3x^2\right)-\left(8x^2+6x\right)+\left(12x+9\right)\)
\(=x^2\left(4x+3\right)-2x\left(4x+3\right)+3\left(4x+3\right)\)
\(=\left(4x+3\right)\left(x^2-2x+3\right)\)
Câu b : \(5x^3-12x^2+14x-4\)
\(=5x^3-10x^2-2x^2+10x+4x-4\)
\(=\left(5x^3-2x^2\right)-\left(10x^2-4x\right)+\left(10x-4\right)\)
\(=x^2\left(5x-2\right)-2x\left(5x-2\right)+2\left(5x-2\right)\)
\(=\left(5x-2\right)\left(x^2-2x+2\right)\)
Câu c : \(x^3-5x^2+2x+8\)
\(=x^3+x^2-6x^2-6x+8x+8\)
\(=\left(x^3+x^2\right)-\left(6x^2+6x\right)+\left(8x+8\right)\)
\(=x^2\left(x+1\right)-6x\left(x+1\right)+8\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-6x+8\right)\)
\(=\left(x+1\right)\left[x^2-2x-4x+8\right]\)
\(=\left(x+1\right)\left[x\left(x-2\right)-4\left(x-2\right)\right]\)
\(=\left(x+1\right)\left(x-2\right)\left(x-4\right)\)
Câu d : \(4x^3+5x^2+10x-12\)
\(=4x^3+8x^2-3x^2+16x-6x-12\)
\(=\left(4x^3-3x^2\right)+\left(8x^2-6x\right)+\left(16x-12\right)\)
\(=x^2\left(4x-3\right)+2x\left(4x-3\right)+4\left(4x-3\right)\)
\(=\left(4x-3\right)\left(x^2+2x+4\right)\)
a: \(12x^3-6x^2+3x\)
\(=3x\cdot4x^2-3x\cdot2x+3x\cdot1\)
\(=3x\left(4x^2-2x+1\right)\)
b: \(\dfrac{2}{5}x^2+5x^3+x^2y\)
\(=x^2\cdot\dfrac{2}{5}+x^2\cdot5x+x^2\cdot y\)
\(=x^2\left(\dfrac{2}{5}+5x+y\right)\)
c: \(14x^2y-21xy^2+28x^2y^2\)
\(=7xy\cdot2x-7xy\cdot3y+7xy\cdot4xy\)
\(=7xy\left(2x-3y+4xy\right)\)
1) \(x^2-6x+3\)
\(=x^2-6x+9-6\)
\(=\left(x-3\right)^2-6\)
\(=\left(x-3+\sqrt{6}\right)\left(x-3-\sqrt{6}\right)\)
2) \(2m^2+10m+8\)
\(=2m^2+2m+8m+8\)
\(=2m\left(m+1\right)+8\left(m+1\right)\)
\(=\left(2m+8\right)\left(m+1\right)\)
\(=2\left(m+4\right)\left(m+1\right)\)
3) \(9x^2+6x-8\)
\(=\left(9x^2+6x+1\right)-9\)
\(=\left(3x+1\right)^2-9\)
\(=\left(3x+4\right)\left(3x-2\right)\)
4) \(x^3-5x^2-14x\)
\(=x\left(x^2-5x-14\right)\)
\(=x\left(x^2-2x+7x-14\right)\)
\(=x\left[x\left(x-2\right)+7\left(x-2\right)\right]\)
\(=x\left(x+7\right)\left(x-2\right)\)
6x3 - 7x2 + 5x - 2
= 6x3 - 4x2 - 3x2 + 2x + 3x - 2
= 6x2(x - 2/3) - 3x(x - 2/3) + 3(x - 2/3)
= (x - 2/3)(6x2 - 3x + 3)
= 3(x - 2/3)(2x2 - x + 1)
4x3 + 5x2 + 10x - 12
= 4x3 - 3x2 + 8x2 - 6x + 16x - 12
= 4x2(x - 3/4) + 8x(x - 3/4) + 16(x - 3/4)
= (x - 3/4)(4x2 + 8x + 16)
= 4(x - 3/4)(x2 + 2x + 4)
4x3 - 7x2 - x + 3
= 4x3 - 3x2 - 4x2 + 3x - 4x + 3
= 4x2(x - 3/4) - 4x(x - 3/4) - 4(x - 3/4)
= (x - 3/4)(4x2 - 4x - 4)
= 4(x - 3/4)(x2 - x - 1)
4x3 - 5x2 + 6x + 9
= 4x3 + 3x2 - 8x2 - 6x + 12x + 9
= 4x2(x + 3/4) - 8x(x + 3/4) + 12(x + 3/4)
= (x + 3/4)(4x2 - 8x + 12)
= 4(x + 3/4)(x2 - 2x + 3)
3x3 - 5x2 + 5x - 2
= 3x3 - 2x2 - 3x2 + 2x + 3x - 2
= 3x2(x - 2/3) - 3x(x - 2/3) + 3(x - 2/3)
= (x - 2/3)(3x2 - 3x + 3)
= 3(x - 2/3)(x2 - x + 1)
\(a,2x^3+5x^2+5x+3\)
\(=2x^3+3x^2+2x^2+3x+2x+3\)
\(=x^2\left(2x+3\right)+x\left(2x+3\right)+\left(2x+3\right)\)
\(=\left(2x+3\right)\left(x^2+x+1\right)\)
\(\left(5x^3+14x^2+12x+8\right):\left(x+2\right).\)
\(=\left(5x^3+10x^2+4x^2+8x+4x+8\right):\left(x+2\right)\)
\(=\left[5x^2\left(x+2\right)+4x\left(x+2\right)+4\left(x+2\right)\right]:\left(x+2\right)\)
\(=\left(x+2\right).\left(5x^2+4x+4\right):\left(x+2\right)\)
\(=5x^2+4x+4\)